Comparison of three technics for collection of preputial samples for the diagnosis of campylobacteriosis - Ramos, Auvanir de A.; Guida, Hélio Gustavo; Andrade, Vania Lucia B. (Pesquisa Agropecuaria Brasileira, 2014)
Using six bulls naturally infected with Campylobacter fetus, three technics for collection of preputial samples for bacteriological examination were compared: the first technic consisted in utilizing a plastic pipette and bulb of artificial insemination Bartlett et al. (1947), to aspirate material; the second, using a "swab" Gibson et al. (1970), adaptated to a plastic pipette of artificial insemination was used to scrub the preputial cavity mucosa; the third technic involves the washing of the preputial cavity with the aid of a G.M. apparatus Mello (1953), with tripticase broth. Bacteriological examination of the samples shows conclusively that aspirating was the technic of choice because it permits the identification of more Campylobacter fetus positive samples besides less interference from contaminating organisms.